2009
DOI: 10.1016/j.jtcvs.2008.10.010
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical valves versus the Ross procedure for aortic valve replacement in children: Propensity-adjusted comparison of long-term outcomes

Abstract: Results from this study showed good outcomes and an acceptable complication rate with both valve choices. Given the significantly increased risk of early and late death in younger children receiving smaller mechanical valves, the Ross procedure confers survival advantage in this age group at the expense of increased reoperation risk, especially in patients with a rheumatic cause.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
67
1
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 25 publications
(46 reference statements)
4
67
1
1
Order By: Relevance
“…Wilder et al [1] have reported an important series of 90 children operated for significant aortic regurgitation in recent years in a single institution. The children received either aortic valve repair (51%), the Ross procedure (23%) or valve replacement with a prosthesis [aortic valve replacement (AVR), 26%].…”
Section: Conflict Of Interest: None Declaredmentioning
confidence: 99%
See 1 more Smart Citation
“…Wilder et al [1] have reported an important series of 90 children operated for significant aortic regurgitation in recent years in a single institution. The children received either aortic valve repair (51%), the Ross procedure (23%) or valve replacement with a prosthesis [aortic valve replacement (AVR), 26%].…”
Section: Conflict Of Interest: None Declaredmentioning
confidence: 99%
“…Mechanical and bioprosthetic aortic valve replacement (AVR) may result in patient-prosthesis size mismatch, prosthesis outgrowth and lifestyle limitations or complications resulting from anticoagulation [1]. Ross procedures (AVR using pulmonary autograft) provide solutions to some of these limitations in that the autograft continues to grow and does not require anticoagulation.…”
Section: Introductionmentioning
confidence: 99%
“…Although mechanical valves are durable, they have many disadvantages including the necessity for life-long anticoagulation, risks of endocarditis, bleeding, and thromboembolic events. [6,7] Even reoperation is required in at least 10% of mechanical valves by 20 years for endocarditis, paravalvular leak, thrombotic, or hemorrhagic complications or pannus formation with obstruction. Mechanical valves are also more problematic in female patients in childbearing age who need aortic valve replacement, leading to severe social and psychological distress.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical valves are also more problematic in female patients in childbearing age who need aortic valve replacement, leading to severe social and psychological distress. [6,7] Although bioprosthetic valves do not require anticoagulation, their long-time durability is not optimal in young patients. [4] The ideal valve substitute in children, therefore, should have somatic growth, no need for anticoagulation with excellent hemodynamic properties, resistance to infection, and long-term durability.…”
Section: Discussionmentioning
confidence: 99%
“…Although current mechanical and biological heart valve replacements improve patient survival and quality of life, problems such as thrombosis, infection and limited durability still occur and none of the current conventional valve replacements has the capacity to grow in young patients (Alpert and Dalen, 1987;Roudaut et al, 2007;Kidane et al, 2009). For young patients under the age of 18 years with severe aortic heart valve disease, the Ross procedure using a pulmonary autograft is the preferred replacement valve substitute (Alsoufi et al, 2009). A cryopreserved pulmonary allograft is then implanted in the right ventricular outflow tract (RVOT), although these have limitations including variability in their durability.…”
Section: Introductionmentioning
confidence: 99%